De novo transcriptome sequence and identification of major bast-related genes involved in cellulose biosynthesis in jute (Corchorus capsularis L.). (December 2015) - Zhang, Liwu; Ming, Ray; Zhang, Jisen; Tao, Aifen; Fang, Pingping; Qi, Jianmin
Abstract Background Jute fiber, extracted from stem bast, is called golden fiber. It is essential for fiber improvement to discover the genes associated with jute development at the vegetative growth stage. However, only 858 EST sequences of jute were deposited in the GenBank database. Obviously, the public available data is far from sufficient to understand the molecular mechanism of the fiber biosynthesis. It is imperative to conduct transcriptomic sequence for jute, which can be used for the discovery of a number of new genes, especially genes involved in cellulose biosynthesis. Results A total of 79, 754, 600 clean reads (7.98 Gb) were generated using Illumina paired-end sequencing. De novo assembly yielded 48, 914 unigenes with an average length of 903 bp. By sequence similarity searching for known proteins, 27, 962 (57.16 %) unigenes were annotated for their function. Out of these annotated unigenes, 21, 856 and 11, 190 unigenes were assigned to gene ontology (GO) and euKaryotic Ortholog Groups (KOG), respectively. Searching against the Kyoto Encyclopedia of Genes and Genomes Pathway database (KEGG) indicated that 14, 216 unigenes were mapped to 268 KEGG pathways. Moreover, 5Susy, 3UGPase, 9CesA, 18CSL, 2Kor (Korrigan ), and 12Cobra unigenes involving in cellulose biosynthesis were identified. Among these unigenes, the unigenes of comp11264_c0 (SuSy ), comp24568_c0 (UGPase ), comp11363_c0 (CesA ), comp11363_c1 (CesA ), comp24217_c0 (CesA ), and comp23531_c0 (CesA ), displayed relatively high expression level in stem bast using FPKM and RT-qPCR, indicating that they may have potential value of dissecting mechanism on cellulose biosynthesis in jute. In addition, a total of 12, 518 putative gene-associate SNPs were called from these assembled uingenes. Conclusion We characterized the transcriptome of jute, discovered a broad survey of unigenes associated with vegetative growth and development, developed large-scale SNPs, and analyzed the expression patterns of genes involved in cellulose biosynthesis for bast fiber. All these provides a valuable genomics resource, which will accelerate the understanding of the mechanism of fiber development in jute.